Znaczenie biocybernetyki w nauczaniu inżynierii biomedycznej na podstawie opinii studentów - Tadeusiewicz , Ryszard (Studia Edukacyjne, 2022)
Teaching Biomedical Engineering now takes place in most technical schools and in some universities. Each of them uses its own curricula, tailored to the goals of education and the qualifications of their staff. This diversity concerns, among other things, the lecture on the subject of biocybernetics. At the birth of the Biomedical Engineering studies (which was launched at the AGH University of Science and Technology a year earlier than in all other Polish universities), the biocybernetics lecture was the first one that the students listened to. Following the example of AGH, other universities also introduced this lecture. Later, however, many universities gave up teaching this subject, and Act 2.0 changed the name of the scientific discipline for many years called “Biocybernetics and Biomedical Engineering” to “Biomedical Engineering”, limiting the chances of obtaining degrees in biocybernetics. Nevertheless, at AGH UST, this subject is still taught at the beginning of the Biomedical Engineering course. In the academic year 2021/22, a survey was conducted among the students; having had one semester of lectures, they answered the question: “How will the knowledge of biocybernetics help me in the profession of a biomedical engineering specialist?” This article presents the results of this survey and encourages you to think about it.